Inflammation and risk of recurrent cardiovascular events according to prior vascular disease location. (3rd October 2022) - Burger, P M; Ridker, P; Dorresteijn, J; Koudstaal, S; Mosterd, A; Pradhan, A; Visseren, F
Abstract: Background: In recent years, anti-inflammatory drugs have been shown to reduce the risk of recurrent cardiovascular disease (CVD) events in patients with coronary artery disease (CAD), but have not yet been tested in patients with other vascular disease locations. Whether the relation between inflammation and recurrent CVD is modified by prior vascular disease location is unknown. Purpose: This study aimed to establish the relation between low-grade inflammation and recurrent CVD according to prior vascular disease location. Methods: Inflammation was measured by plasma concentrations of high-sensitivity C-reactive protein (CRP). Patients from the UCC-SMART cohort with CAD (n=4, 517), cerebrovascular disease (CeVD; n=2, 154), peripheral artery disease (PAD, n=1, 154), or abdominal aortic aneurysm (AAA, n=424), and CRP ≤10 mg/L were included in the main analysis (combined n=8, 249). Patients with CRP >10 mg/L (n=756) were analysed separately. The primary outcome was a composite of myocardial infarction, ischemic stroke, or cardiovascular death. Secondary outcomes included the primary outcome components, major adverse limb events (MALE), and all-cause mortality. The relation between CRP and outcomes was assessed using Cox proportional hazard models stratified by prior vascular disease location, and adjusted for potential confounders. Results: During a median follow-up of 9.5 years (interquartile range 5.1–13.9) 1, 877 CVD events, 887 MALE events, and 2, 341 deaths were observed. In the total population, CRP was related to recurrent CVD (hazard ratio [HR] per 1 mg/L 1.08; 95% confidence interval [CI] 1.05–1.10), and all secondary outcomes except for ischemic stroke (HR 1.03; 95% CI 0.99–1.08). Compared to the first quintile of CRP, HRs for recurrent CVD were 1.66 (95% CI 1.41–1.96) for the last quintile ≤10 mg/L, and 1.97 (95% CI 1.64–2.36) for the subgroup with CRP >10 mg/L. CRP was related to recurrent CVD in patients with CAD (HR per 1 mg/L 1.08; 95% CI 1.04–1.11), as well as CeVD (HR 1.05; 95% CI 1.01–1.10), PAD (HR 1.08; 95% CI 1.03–1.13), and AAA (HR 1.08; 95% CI 1.01–1.15; p for interaction 0.815). The relation between CRP and all-cause mortality was stronger for patients with CAD (HR 1.13; 95% CI 1.09–1.16) compared to other locations (HRs 1.06–1.08; p=0.002). Conclusion: Inflammation is an independent risk factor of recurrent CVD and mortality, irrespective of prior vascular disease location. Trials of anti-inflammatory drugs in patients with CeVD, PAD, and AAA are warranted. Funding Acknowledgement: Type of funding sources: None.